Analysis of Understanding and Belief in Interest in Becoming a Sharia Insurance Participant with Public Perception as an Intervening Variable - Harahap, Yusra Lestari; Syarvina, Wahyu; Imsar, Imsar (Almana : Jurnal Manajemen dan Bisnis, 2025)
This research is motivated by the low public understanding and trust in insurance, even though this insurance is very important for future life. This study aims to analyze the influence of public understanding and trust on the interest in becoming a Sharia insurance participant, with public perception as an intervening variable. The study was conducted in the rural area of Sibuhuan, Padang Lawas, considering the low penetration of Sharia insurance due to low public understanding and trust. A sample of 100 respondents was drawn from a population of 22,464 people, referring to the age distribution of BPS 2024–2025. Analysis using SmartPLS 4 showed that understanding and trust significantly influenced interest, with trust as the dominant factor. Public perception was proven to strengthen the relationship between understanding and trust on interest in participating in Sharia insurance.